Optimal Multi-Objective Reconfiguration in distribution systems using the Novel Intelligent Water Drops approach - Hajar Bagheri Tolabi; Mohd Hasan Ali (Majlesi Journal of Electrical Engineering)
This paper presents a new method for optimal multi-objective reconfiguration of distribution system based on the novel Intelligent Water Drops (IWD) algorithm in order to mitigation of losses, improving the voltage profile and equalizing the feeder load balancing. The proposed method is validated at nominal load by implementing on a 33 bus test system. The obtained results prove the proposed technique is more accurate than other well known methods such as Genetic Algorithm, Particle Swarm Optimization, and Harmony Search algorithm meanwhile it has an efficient convergence property in compared with other intelligent search algorithms.